Pengujian Aktivitas Antioksidan Kombinasi Ekstrak Metanol Daun Mangga Gadung (Mangifera indica L. var. gadung) dan Ekstrak Etanol Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) (Antioxidant Activity Assay of Methanolic Extract of Gadung Mango Leaves (Mangifera indica L. var. gadung) and Ethanolic Extract of Pandan Leaves (Pandanus amaryllifolius Roxb.) Combination) - Dewi Kusumaningrum Pamungkas; Yuni Retnaningtyas; Lestyo Wulandari (Pustaka Kesehatan, 2017)
The content of polyphenolic compounds in mango and fragrant pandan leaves has been showed an antioxidant activity and commonly used as traditional treatment of some diseases. The aim of this research was to determine the activity of antioxidant of the gadung mango leaves and fragrant pandan leaves extract combination. The activity of antioxidant was investigated by DPPH method (IC50) with vitamin C as positive control. The results showed that the sample had lower antioxidant activities than vitamin C. The IC50 value of vitamin C was 2.613±0.021 μg/ml, followed by methanolic extract of gadung mango leaves, ratio 1:1 of gadung mango leaves extract and pandan leaves extract combination, and ethanolic extract of fragrant pandan leaves with IC50 value of 3.263±0.009; 13.392±0.157; 39.700±1.003 μg/ml, respectively. Methanolic extract of gadung mango leaves and ethanolic of fragrant pandan leaves combination didn't have higher antioxidant activities compared to the antioxidant activities of the singular methanolic extract of gadung mango leaves itself. Keywords: antioxidant activity, gadung mango, fragrant pandan